Pelatihan Penggunaan Excel Untuk Pengelolaan Data Pada Tingkat RW Pada Balai RW 08 Duri Pulo Kecamatan Gambir - Ika Susanti; Sejati Waluyo; Ferdiansyah (CV. Multi Kreasi Media, 2024)
In carrying out RW tasks related to data management. Both budget data, population data, and correspondence needs. It is a challenge to manage the data more effectively and efficiently by utilizing existing technology. This training aims to improve the ability of RW 08 Duri Pulo administrators, Gambir District, to use Microsoft Excel to help manage data at the RW level. The training includes basic functions in Excel, report data management, and how to use pivot tables for various needs. Excel data is also provided in the training that can be used as training material. This training is expected to provide an interesting and enjoyable experience in using Excel for tasks at the RW level. Along with the use of Excel to facilitate the work of RW 08 Duri Pulo officers, it is hoped that it will be able to improve the services RW administrators provide to the community.